Diffuse choroid plexus hyperplasia: an under-diagnosed cause of hydrocephalus in children? - Abd. Aziz, Azian; Coleman, Lee; Morokoff, Andrew; Maixner, Wirginia (Springer, 2005)
Hydrocephalus is a common neurological disorder in children and the result of a variety of causes. However, with the advancement of imaging modalities, particularly MRI, previously reported rarer causes of hydrocephalus in children are now being more readily appreciated. We report an 11-year-old boy with diffuse villous hyperplasia of the choroid plexus. He had a ventriculo-peritoneal (VP) shunt in-situ and a prior diagnosis from infancy of congenital aqueduct stenosis as the cause of his hydrocephalus. His current presentation was with further shunt dysfunction. CT and MRI demonstrated enlarged choroid plexuses but did not confirm aqueduct stenosis. CSF overproduction was demonstrated from the externalized ventricular drain. The enlarged choroid plexuses were surgically resected and histology confirmed choroid plexus hyperplasia. Identification of choroid plexus hyperplasia is important since the neurosurgical management of hydrocephalus is not VP shunt insertion, but resection of the hyperplastic choroid plexus.